The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00421-010-1776-0
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous changes in heart rate regulation due to mental load in simulated office work

Abstract: The cardiac regulation effects of a mental task added to regular office work are described. More insight into the time evolution during the different tasks is created by using time-frequency analysis (TFA). Continuous wavelet transformation was applied to create time series of instantaneous power and frequency in specified frequency bands (LF 0.04-0.15 Hz; HF 0.15-0.4 Hz), in addition to the traditional linear heart rate variability (HRV) parameters. In a laboratory environment, 43 subjects underwent a protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 40 publications
8
112
3
Order By: Relevance
“…Other studies show that students who have the most intense cardiovascular responses around the time of examination and/or during examination may be at risk for developing cardiovascular disease or cardiac event in later life (Loyke, 1995;Stewart and Barnet, 2008;Xavier et al, 2009;Taelman et al, 2011;Hjovtskov et al, 2004). In some studies, mental work has been found to cause increases in heart rates (HR) (Ross, 2001;Martic et al, 2008;Hjortskpv 2004) and blood pressures among students (Hughes, 2004), while elevations in systolic blood pressure (SBP) was linked with academic stress around the period of semester examination, and no such link was observed for diastolic blood pressure (DBP) or HR in another study (Conley and Lehman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that students who have the most intense cardiovascular responses around the time of examination and/or during examination may be at risk for developing cardiovascular disease or cardiac event in later life (Loyke, 1995;Stewart and Barnet, 2008;Xavier et al, 2009;Taelman et al, 2011;Hjovtskov et al, 2004). In some studies, mental work has been found to cause increases in heart rates (HR) (Ross, 2001;Martic et al, 2008;Hjortskpv 2004) and blood pressures among students (Hughes, 2004), while elevations in systolic blood pressure (SBP) was linked with academic stress around the period of semester examination, and no such link was observed for diastolic blood pressure (DBP) or HR in another study (Conley and Lehman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This activation can be affected by the individual's breathing (Taelman et al, 2011). Hjortskov et al (2004) observed that mental stress during computer work leads to changes in HR and to a sustained increase in BP, and that these effects are reverted resting (Paschoal et.…”
Section: Methodsmentioning
confidence: 99%
“…Fischer et al (2012) state that information reduction is a most important aspect of coping with complexity within problem solving as great amounts of information may overstrain human processing capacity. In that regard, cognitive load theory recognizes two main sources of stress-inducing potentials: the intrinsic cognitive load of a problem, referring to the internal structure of the information that is given to the problem solver and that he or she needs to acquire to reach the intended goal, and the extraneous cognitive load, associated not with the inherent structure of the problem-related information, but with the manner of its presentation (Sweller 1988;Sweller et al 2011;see Bley et al (2015) for an application of cognitive load theory in the context of VET).…”
Section: Stress-inducing Potentials Of Problem-solving Activitiesmentioning
confidence: 99%
“…Existing studies show that both HR (e.g., Clays et al 2011;Hjortskov et al 2004;Taelman et al 2011) and skin conductance (e.g., Reinhardt et al 2012) increase in response to mental stress. The LF/HF ratio shows an increase under stress, which indicates a predominant state of the sympathetic nervous system under stress-inducing conditions (e.g., Hjortskov et al 2004;Isowa et al 2006).…”
Section: Stress-inducing Potentials Of Problem-solving Activitiesmentioning
confidence: 99%